PENGARUH UKURAN HOST TERHADAP MUTU FISIK DAN PROFIL DISOLUSI TABLET CAMPURAN INTERAKTIF NIFEDIPIN - Ilham Kuncahyo; Siti Aisiyah; Shabrina Nindya Hutami; Raden Roro Sri Wulandari (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2025)
Homogeneity remains a significant challenge in the production of tablets containing low-dose active pharmaceutical ingredients such as nifedipine. According to the Biopharmaceutics Classification System (BCS), nifedipine is categorized as a BCS Class II drug, characterized by high permeability but low solubility. The use of an interactive mixture method between a large host as a carrier and a micronized drug/active substance that is interactively attached to the host is an innovation to prevent this problem. This study aims to evaluate the effect of varying host particle sizes on the homogeneity, physical quality, and dissolution profile of nifedipine interactive mixture tablets. Five tablet formulations were developed, each employing different host particle sizes: formula 1 (16/40 mesh), formula 2 (18/40 mesh), formula 3 (20/40 mesh), formula 4 (25/40 mesh), and formula 5 (30/40 mesh). The host carrier was prepared by mixing Avicel PH 101 and lactose in a 1:1 ratio, followed by granulation using PVP as a binder. Tablet production was conducted via direct compression, involving a one-hour mixing of nifedipine with each host size (homogeneity test), followed by a five-minute mixing with magnesium stearate prior to compression. The resulting tablets were evaluated for their physical quality, including friability, hardness, disintegration time, and dissolution rate. The findings indicated that host particle size significantly influenced both the physical characteristics and the dissolution behavior of the nifedipine interactive mixture tablets. Among all formulations, formula 5, with a 30/40 mesh host particle size, yielded tablets with greater hardness, lower friability, and an enhanced dissolution rate compared to formula 1 (16/40 mesh), formula 2 (18/40 mesh), formula 3 (20/40 mesh) dan formula 4 (25/40 mesh).